"Senegalia massiliensis, " a new bacterium isolated from the human gastrointestinal tract. (July 2016) - Traore, S.I.; Cadoret, F.; Fournier, P.E.; Raoult, D.
Abstract: We report the main characteristics of "Senegalia massiliensis" strain SIT17 (= CSUR P2130) that was isolated from the stool of a healthy 13-month-old Senegalese boy.